Homeless-Youth Education and Its Hidden Capitalism: a Composite Case Study in North America - Domum Qualiter; Sarah Neuman (International Journal of Qualitative Research, 2023)
This research aims to understand why after establishing educational programs intended for youth at-risk of being homeless in inner-city urban contexts, youth still turn to homelessness in North America. This article describes a composite case study of three cities in North America to ensure the anonymity of all stakeholders, key informants, and practitioners providing qualitative data. The results show that the internal management of education programs-specifically, youth's potential behavior in three categories: violence, substance use, and intimate relationships are challenges that prevent organizations from successfully retaining youth engagement in education. More importantly, capitalism related to the street-trades is discussed as the key cause of persistent youth homelessness. Protecting youth from homelessness and ensuring access to compulsory public education must seek to identify mechanisms through which homeless youth can be exploited for profit. Addressing hidden structures of capitalism within homelessness in North America supports the prevention of chronic homelessness and disempowered life trajectories.